Overcoming the challenges facing Nepal's health system during federalisation: an analysis of health system building blocks - Sharada Prasad Wasti; Edwin van Teijlingen; Simon Rushton; Madhusudan Subedi; Padam Simkhada; Julie Balen; for the Nepal Federal Health System Team (BMC, 2023)
Abstract Introduction Nepal's move to a federal system was a major constitutional and political change, with significant devolution of power and resources from the central government to seven newly created provinces and 753 local governments. Nepal's health system is in the process of adapting to federalism, which is a challenging, yet potentially rewarding, task. This research is a part of broader study that aims to explore the opportunities and challenges facing Nepal's health system as it adapts to federalisation. Methods This exploratory qualitative study was conducted across the three tiers of government (federal, provincial, and local) in Nepal. We employed two methods: key informant interviews and participatory policy analysis workshops, to offer an in-depth understanding of stakeholders' practical learnings, experiences, and opinions. Participants included policymakers, health service providers, local elected members, and other local stakeholders. All interviews were audio-recorded, transcribed, translated into English, and analysed thematically using the six WHO (World Health Organization) health system building blocks as a theoretical framework. Results Participants noted both opportunities and challenges around each building block. Identified opportunities were: (a) tailored local health policies and plans, (b) improved health governance at the municipality level, (c) improved health infrastructure and service capacity, (d) improved outreach services, (e) increased resources (health budgets, staffing, and supplies), and (f) improved real-time data reporting from health facilities. At the same time, several challenges were identified including: (a) poor coordination between the tiers of government, (b) delayed release of funds, (c) maldistribution of staff, (d) problems over procurement, and (e) limited monitoring and supervision of the quality of service delivery and data reporting. Conclusion Our findings suggest that since federalisation, Nepal's health system performance is improving, although much remains to be accomplished. For Nepal to succeed in its federalisation process, understanding the challenges and opportunities is vital to improving each level of the health system in terms of (a) leadership and governance, (b) service delivery, (c) health financing, (d) health workforce, (e) access to essential medicines and technologies and (f) health information system.